Urban Micro-Living Single-Room Occupancy (SRO) Units for Lower-Middle-Income White-Collar Workers in the Cubao CBD - Lau, Engelbert U.; Araneta, Maureen Anne L.
This comprehensive design project aims to maximize the populated space of the Cubao Business District, one of the busiest commercial hubs in the metro. In order to create a low-cost and space-efficient SRO unit and building design, the following steps were taken: (1) data gathering through interviews with existing lower-middle-income white-collar workers in Cubao to understand their needs, (2) design adherence to the standards outlined in the National Building Code and Neufert Architects Data on anthropometric standards to ensure safety and comfort,
and (3) balancing both space-efficiency as well as optimization of orientation and spacing for improved natural light and ventilation. The very employees who contribute to the economic growth and vitality of the community are often overlooked. There is a shortage of comfortable and affordable housing options within the CBD which drives lower-middle-income white-collar workers to look for homes in far-flung locations and/or stay in capsule-sized rooms, crammed boarding houses, and other shared spaces without privacy. The SRO concept is a stride towards bridging a gap, providing this demographic with a viable solution that not only
meets their budget constraints but also recognizes their need for personal space and comfort. The overarching goal of this project is to design a living environment that goes beyond being merely habitable; it becomes a space that is humane and conducive to rest and well-being.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Single-room occupancy hotels -- Cubao; Single people -- Housing -- Cubao; Low-income housing -- Cubao; Living alone -- Cubao; City planning -- Economic aspects -- Cubao; Architecture and society